The impact of various nanofluid types on triangular microchannels heat sink cooling performance - Mohammed H.A.; Gunnasegaran P.; Shuaib N.H. (2023)
This paper discusses the impact of using various types of nanofluids on heat transfer and fluid flow characteristics in triangular shaped microchannel heat sink (MCHS). In this study, an aluminum MCHS performance is examined using water as a base fluid with different types of nanofluids such as Al2O3, Ag, CuO, diamond, SiO2, and TiO2 as the coolants with nanoparticle volume fraction of 2%. The three-dimensional steady, laminar flow and heat transfer governing equations are solved using the finite volume method. It is inferred that diamond-H2O nanofluid has the lowest temperature and the highest heat transfer coefficient, while Al2O3-H2O nanofluid has the highest temperature and the lowest heat transfer coefficient. SiO2-H2O nanofluid has the highest pressure drop and wall shear stress while Ag-H2O nanofluid has the lowest pressure drop and wall shear stress among other nanofluid types. Based on the presented results, diamond-H2O and Ag-H2O nanofluids are recommended to achieve overall heat transfer enhancement and low pressure drop, respectively, compared with pure water. 2011 Elsevier Ltd.